The relationship between workload and musculoskeletal complaints among opak factory workers in Sukaraya Bakti Village, Pancur Batu - Hutapea, Johnson; Pakpahan, Estriyana; Rosari, Anita; Meilani, Inda Kania; Yensuari, Yensuari; Yani, Herlina; Rahimi, Armon; Rajagukguk, Samuel Joshua Hamonangan Tua; Amir, Dwi Fenny; Alponso, Rudolf; Elizabeth, Monalisa (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Based on industrial processes that still use semi-automatic processes, this often causes health problems, such as musculoskeletal problems or disorders in workers due to semi-automatic production processes and heavy loads. The aim is to find out the relationship between workload and musculoskeletal complaints in Opak Village factory workers. Sukaraya Bakti, District. Pancur Batu, Kab. Deli Serdang. The research method carried out here is quantitative descriptive research. Where this research tries to explore how and why this health phenomenon occurs. This descriptive research was carried out using observation and interview methods. Observations and interviews were carried out on several behavioral factors, which were then linked to musculoskeletal complaints in opak makers. It can be concluded that there is a significant relationship between workload and complaints of musculoskeletal disorders among Opak Factory Workers in Sukaraya Bakti Village, Pancur Batu District, Deli Serdang Regency.